Civil Procedure: Access to Commercial Justice - Butler, Petra,; Colley, Allanah, (International Law E-Books Online, Collection 2025., 2025)
The financial burden of litigation continues to be the single most important consideration for parties in determining whether to fight their case in court. The financial burden of embarking on civil litigation can influence litigation strategy and determine who has, and who is denied, access to justice. This edition provides a comprehensive study of the financial obstacles of access to justice in civil litigation. It draws on the contributions of eighteen jurisdictions to examine what impact the commitment to access to justice has made regarding access to civil litigation.